The Spin-Off of Scientific Services of Novartis into a New, Independent Technology Company Offering Services to the Pharmaceutical, Chemical, and Nutrition Industry - Hans-Ulrich Blaser; Martin Studer (CHIMIA, 1999)
Starting on October 1, 1999, the three sections 'Central Analytics', 'Physics', and 'Catalysis Synthesis Services' of the Scientific Services of Novartis will operate as an independent company. The new company will have about 180 employees and will offer services to customers in the pharmaceutical, chemical, and nutrition industry as well as to authorities and service firms active in these fields. The focus of activities for the new company is the chemical and physical characterization (analytics), optimization of products and processes, and the development and application of special synthetic methods, in particular by utilizing catalysis. Support is offered via single services, comprehensive service packages, or by taking over assignments for entire areas. The combination of a high scientific and technical standard built up on an ISO 9001 quality-management system, including cGMP and GLP, with an attractive working environment will be the basis for an innovative center of chemical and physical expertise.